Rhetorical Categories of Ethos, Logos and Pathos: Sounding Judicial Speech of Lawyers - YAKUTINA, M.V.; MILYAEVA, L.V.; TARASOVA, L.Y.; ROSTOVTSEVA, P.P. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents a phonetic comparative analysis of sounding judicial speech based on three classical rhetorical categories: ethos, logos, pathos. The material includes authentic audio recordings of court speeches by American lawyers with the necessary professional and general cultural competences in the US Supreme Court, which was reflected at the prosodic level of their speech. The vivid, influencing speech nature based on pathos and ethos, polemic, and suggestive discourse based on logos are reflected not only in the variability of basic frequency but in various dynamic and temporal characteristics, depending on the rhetorical category on which they were based. RESUMEN El artículo presenta un análisis fonético comparativo del sonido del discurso judicial basado en tres categorías retóricas clásicas: ethos, logos, pathos. El material incluye grabaciones de audio auténticas de discursos de la corte de abogados estadounidenses con las competencias culturales profesionales y generales necesarias en la Corte Suprema de los Estados Unidos, que se reflejó en el nivel prosódico de su discurso. La naturaleza del discurso vívida e influyente basada en el pathos y el ethos, el discurso polémico y sugestivo basado en logos se refleja no solo en la variabilidad de la frecuencia básica, sino en diversas características dinámicas y temporales, dependiendo de la categoría retórica.